Architecture now!. 4 - Jodidio, Philip (Kèoln ; London : Taschen, 2010)
This volume identifies the latest trends from Los Angeles to Tokyo and explains exactly how architecture is finding a new equilibrium, where the old boundaries of space and function no longer exist.
Includes index.
Keywords: Architecture, Modern -- 20th century; Architecture, Modern -- 20th century -- Pictorial works